The Damage of the Crayfish (Procambarus Clarkii) Digestive Organs Caused by Citrobacter Freundii Is Associated With the Disturbance of Intestinal Microbiota and Disruption of Intestinal-Liver Axis Homeostasis - Li, Minghao; Wang, Jincheng; Deng, Huiling; Li, Liangyu; Huang, Xiaoli; Chen, Defang; Ouyang, Ping; Geng, Yi; Yang, Shiyong; Yin, Lizi; Luo, Wei; Jiang, Jun (Frontiers in Cellular and Infection Microbiology, 2022)
As a common conditional pathogenic bacterium in nature, C. freundii has posed a threat to crayfish culture and may infect humans through consumption. However, the pathogenic mechanism of C. freundii in crayfish remains unknown, which poses difficulties for the prevention and control of the bacterium. In this study, the effects of C. freundii on the digestive organs, intestine and hepatopancreas, of crayfish were investigated by high-throughput sequencing technology combined with histological analysis and flow cytometry. The findings suggested that C. freundii caused disruption of the intestinal microbiota, leading to intestinal inflammation and disrupting intestinal integrity. Meanwhile, C. freundii infection stimulates bile acid biosynthesis in the intestinal microbiota. Transcriptomic results showed significant upregulation of hepatopancreatic lipid degradation pathway and cytochrome P450-related pathways. Follow-up experiments confirmed a decrease in intracellular lipids and an increase in ROS and apoptosis. All the results indicated the disruption of intestinal-liver axis homeostasis due to disturbed intestinal microbiota may as a potential basis for C. freundii pathopoiesis in crayfish. These results provide new insights into the pathogenic molecular mechanisms of C. freundii in the infection of crayfish.